Opportunities for UK reinsurance broker on Russian insurance market - Rogozin, Konstantin; Vayshnurs, Anton (2006)
Due to positive developments on Russian insurance sector and its great potential an increasing number of international insurance, reinsurance and reinsurance broking companies focus their expansion strategies on Russian market as on one of the regions, which possess a tremendous amount of opportunity.